Skin transcriptomic correlates of cave-dwelling Sinocyclocheilus cavefish - Luo, Xiayue; Chen, Bing; Mao, Tingru; Liu, Yewei; Yang, Jian; Meegaskumbura, Madhava (Frontiers in Ecology and Evolution, 2023)
With 78 species, Sinocyclocheilus cavefish constitute the largest cavefish radiation in the world. They exhibit remarkable morphological diversity across three habitat types: surface (surface morphs, normal-eyed, variably colored), exclusively-cave-dwelling (stygobitic morphs, eyeless, depigmented), and intermediate between cave and surface (stygophilic morphs, micro-eyed, partially depigmented). Distinctive traits of Sinocyclocheilus include variations in eye and skin conditions associated with their habitat, despite the role of the skin in sensing environmental changes, its habitat correlates are less understood, compared to the well-studied eye conditions. Here, we analyzed the correlation between Sinocyclocheilus skin morphology and its habitat, utilizing morphological and transcriptomics-based methods. We generated skin RNA-sequencing data for nine species and integrated those with existing data from five additional species. These 14 species represent the primary clades and major habitats of these cavefish. We identified 7,374 orthologous genes in the skin transcriptome data. Using a comparative transcriptomics approach, 1,348 differentially expressed genes (DEGs) were identified in the three morphotypes. GO and KEGG enrichment analyses suggested that these genes were mainly involved in energy metabolism, immunity and oxidative stress-related functions. Genes related to immune, apoptotic, and necrotic functions were identified through positive selection analysis of orthologous genes. The maximum likelihood phylogenetic tree, based on 1369 single-copy orthologous genes of the species, was largely concordant with the currently established RAD-seq and mt-DNA based phylogenies. Species with higher cave dependence present lighter coloration, fewer dark blotches, and diminished scale morphology and coverage. We also found that differences in skin gene expression and positive selection effects may have contributed to the degradation of skin color and scales. Our study highlights the significance of habitat in shaping skin metabolism, pigmentation variation, and morphology while offering insights into the molecular mechanisms driving these habitat-specific adaptations in Sinocyclocheilus. These findings underscore the transcriptional variation in adapting to diverse environments and contribute to future studies on the evolution and ecology of cavefish.